Inflammatory Myopathies. Issue 6 (December 2022) - Manousakis, Georgios
ABSTRACT: PURPOSE OF REVIEW: This article outlines the salient clinical, serologic, electrophysiologic, imaging, and histopathologic findings and treatment options for the idiopathic inflammatory myopathies, including those related to immune checkpoint inhibitors and SARS-CoV-2. RECENT FINDINGS: The classification of idiopathic inflammatory myopathies has improved with the integration of myositis-specific antibodies and histopathologic findings. Characteristic features of immune checkpoint inhibitor–related myositis have been identified, allowing early recognition and treatment of the syndrome. The COVID-19 pandemic has had a profound impact on the care of patients with idiopathic inflammatory myopathies, and several mechanisms of virus-related muscle injury have been proposed. SUMMARY: A comprehensive evaluation including clinical examination, EMG, imaging, antibody testing, muscle biopsy, and cancer screening, when appropriate, can lead to an earlier accurate diagnosis and an individualized treatment approach for patients with idiopathic inflammatory myopathies.